Diagnosis of celiac disease in clinical practice: Present and future - Elena Crehuá-Gaudiza; Ana Barrés Fernández; Carmen Jovaní Casano; María Latorre Tejerina; Ester María Largo Blanco; María Antonia Moreno Ruiz; Alicia Berghezan Suárez; Mónica García-Peris; Raquel Gil Piquer; Alicia Coret Sinisterra; Sandra Martínez-Barona; Cristina Salido-Capilla; et al. (Elsevier, 2021)
Introduction: European guidelines for the diagnosis of celiac disease (CD) have been updated in 2020. The primary objective was to review the compliance with the diagnostic criteria for CD, according to ESPGHAN 2012. Secondarily, to describe the clinical characteristics of the patients and to assess the changes that would be implied by the application of the new 2020 criteria. Patients and methods: Retrospective multicenter study in which 10 centers participated. Patients from 0 to 16 years old with a new diagnosis of CD in 2018-2019 were included. Clinical, serological variables and the performance of intestinal biopsy (IB) were collected. Results: 163 patients were included (57% female) with a median age of 7.6 years (SD 4.4). The form of presentation was: 47.8% classical, 30.7% no classical and 21.5% asymptomatic, with differences depending on age. Total IgA and anti-transglutaminase IgA antibodies were performed in all centers as the first diagnostic step. IgA anti-endomysial antibodies (EMA) were performed in 80%, and HLA haplotype in 95%. Of the total, 78 cases (47.9%) met criteria for not performing intestinal biopsy (IB). IB was indicated in the remaining 85 patients, but was not performed in 29 cases (17.8%). The performance of IB was lower in the secondary hospitals than in the tertiary ones (p < 0.05).If we applied the ESPGHAN 2020 criteria, we would disregard the HLA study, and 21 more patients would not have required IB (going from 47.9% to 60.7% of the total). Conclusions: Discrepancies are observed in the application of the ESPGHAN 2012 diagnostic criteria due to the different accessibility to EMA and endoscopic IB in secondary centers. With the ESPGHAN-2020 criteria, around 60% of patients will be able to be diagnosed without IB, provided that the determination of EMA is ensured. Resumen: Introducción: Las directrices europeas para el diagnóstico de la enfermedad celiaca (EC) han sido actualizadas en 2020. El objetivo primario fue revisar el grado de cumplimiento de los criterios diagnósticos de EC publicados por la ESPGHAN en 2012. Secundariamente, describir las características clínicas de los pacientes incluidos y valorar los cambios que implicaría la aplicación de los nuevos criterios 2020. Pacientes y métodos: Estudio multicéntrico retrospectivo con participación de 10 centros. Se incluyeron pacientes de 0 a 16 años de nuevo diagnóstico de EC en 2018-2019. Se recogieron variables clínicas, serológicas y realización de biopsia intestinal (BI). Resultados: Incluimos 163 pacientes (57% mujeres), de edad media 7,6 años (DE 4,4). La forma de presentación fue: 47,8% clásica, 30,7% no clásica y 21,5% asintomáticos, con diferencias según la edad. Todos los centros determinaron IgA total y anticuerpos antitransglutaminasa IgA como primer escalón diagnóstico. Los anticuerpos antiendomisio IgA (AAE) se realizaron en el 80% y el haplotipo HLA en el 95%. Del total, 78 casos (47,9%) cumplieron criterios para no realizar BI. En los restantes 85 pacientes estaba indicada BI, no realizándose en 29 casos (17,8%). La realización de BI fue menor en los hospitales secundarios que en los terciarios (p < 0,05).Si aplicáramos los criterios ESPGHAN-2020, prescindiríamos del estudio del HLA y 21 pacientes más no hubieran precisado BI (pasando de un 47,9% a un 60,7% del total). Conclusiones: Se observan discrepancias en la aplicación de los criterios diagnósticos ESPGHAN-2012 debido a la diferente accesibilidad a los AAE y BI endoscópica en centros secundarios. Con los criterios ESPGHAN-2020, en torno a un 60% de los pacientes podrán ser diagnosticados sin precisar BI, siempre que se asegure la determinación de AAE.